Guiding downstream migrating Atlantic salmon Salmo salar and brown trout Salmo trutta of different life stages in a large river using bubbles - Leander, Johan; Hellström, Gustav; Nordin, Jonathan; Jonsson, Micael; Klaminder, Jonatan (2024)
Salmonid repeat spawners are precious individuals for wild populations due to their high fecundity and previous spawning experience, making them important in environmental policy. However, repeat spawners rarely exist above hydropower dams in regulated rivers as the mortality of post-spawners (kelts) when passing through turbines during downstream migration is very high. To mitigate this problem, there are different technical solutions that potentially guide fish toward available fishways. Bubble barriers represent one alternative to costly physical guiding structures, but the efficiency of bubbles for guiding downstream migrating kelts has not been tested. In this study, we evaluate a 100 m long bubble barrier in guiding salmonids-both smolts and kelts-away from the main current and toward an alternative fishway in Ume River, a large regulated river in northern Sweden. We used both acoustic telemetry and sonar to measure the guiding effect of the bubble barrier for downstream migrating fish. We found that more than twice as many salmonids chose the alternative fishway when the bubble barrier was turned on. This was true both for smolts and kelts, suggesting that bubble barriers can be used to guide salmonids of different life stages in rivers with flow rates over 500 m(3) s(-1). Indeed, our study indicates that bubble barriers are low-cost structures that could be rapidly applied in many regulated rivers to support salmonid migration.